Practical program evaluation : theory-driven evaluation and the integrated evaluation perspective - Chen, Huey-tsyh (Los Angeles : SAGE Publications, 2015)
The Second Edition of Practical Program Evaluation shows readers how to systematically identify stakeholders' needs in order to select the evaluation options best suited to meet those needs. Within his discussion of the various evaluation types, Huey T. Chen details a range of evaluation approaches suitable for use across a program's life cycle. At the core of program evaluation is its body of concepts, theories, and methods. This revised edition provides an overview of these, and includes expanded coverage of both introductory and more cutting-edge techniques within six new chapters. Illustrated throughout with real-world examples that bring the material to life, the Second Edition provides many new tools to enrich the evaluator's toolbox.--Publisher website.
Part I: Introduction -- Fundamentals for Program Evaluation -- Understand Approaches to Evaluation and Select Ones That Work: The Comprehensive Evaluation Typology -- Logic Models and the Action Model/Change Model Schema (Program Theory) -- Part II: Program evaluation to help stakeholders develop a program plan -- Helping Stakeholders Clarify a Program Plan: Program Scope -- Helping Stakeholders Clarify a Program Plan: Action Plan -- Part III: Evaluating implementation -- Constructive Process Evaluation Tailored for the Initial Implementation -- Assessing Implementation in the Mature Implementation Stage -- Part IV: Program monitoring and outcome evaluations -- Program Monitoring and the Development of a Monitoring System -- Constructive Outcome Evaluations -- The Experimentation Evaluation Approach to Outcome Evaluation -- The Holistic Effectuality Evaluation Approach to Outcome Evaluation -- The Theory-Driven Approach to Outcome Evaluation -- Part V: Advanced issues in program evaluation -- What to Do if Your Logic Model Does Not Work as Well as Expected -- Formal Theories Versus Stakeholder Theories in Interventions: Relative Strengths and Limitations -- Evaluation and Dissemination: Top-Down Approach Versus Bottom-Up Approach.
Includes bibliographical references (pages 412- 425) and index.
Keywords: Evaluation research (Social action programs)